(untitled) (Journal of Economic Research & Business Administration, 2016)
The question of equitable distribution and assignment of rental income should be viewed with the possibility of its most efficient use in the public interest. The rent is by far one of the sources of economic growth and leverage. The proposed conceptual statements involve enhancing the role of the state in relation to rental industries.